Gastric mucosal inflammation and epithelial cell turnover are associated with gastric cancer in patients with Helicobacter pylori infection. Issue 7 (1st July 2000) - Yoshimura, T; Shimoyama, T; Tanaka, M; Sasaki, Y; Fukuda, S; Munakata, A
Abstract : Background —Infection with a virulent Helicobacter pylori strain is associated with gastric mucosal damage and the increased risk of gastric cancer. Aims —To examine the characteristics of host gastric mucosal responses in patients with gastric cancer, histological grade of gastritis, gastric epithelial apoptosis, and proliferation were studied. Methods —Thirty two patients with early gastric cancer and 32 sex and age matched controls were studied. All subjects were infected with a virulent H pylori strain (vacA s1/m1, cagA positive genotype). Biopsy specimens were taken from the antrum and the corpus of the stomach. The grade of gastritis was assessed according to the updated Sydney system. Apoptotic cells were detected using terminal uridine deoxynucleotidyl nick end labelling, and epithelial cell proliferation was determined by means of the Ki-67 labelling index. Results —In patients with gastric cancer, significantly higher grades were observed when glandular atrophy (p < 0.05) and intestinal metaplasia (p < 0.01) were present in the antrum, and when mononuclear cell infiltration was present in the corpus (p < 0.05). The numbers of apoptotic cells were increased in patients with cancer (p < 0.05) and the apoptotic index correlated significantly with the grade of glandular atrophy. Epithelial cell proliferation was more likely to be increased in mucosa where intestinal metaplasia was present. Conclusions —Infection with H pylori causes increased gastric epithelial apoptosis, resulting in more severe glandular atrophy in patients with gastric cancer. Increased damage of gastric epithelial DNA and the presence of more severe atrophic gastritis might contribute to the development of gastric cancer.